Facial Skin Revitalization with Cohesive Polydensified Matrix-HA20G: Results from a Randomized Multicenter Clinical Study. Issue 12 (December 2021) - Kerscher, Martina; Prager, Welf; Fischer, Tanja C.; Gauglitz, Gerd G.; Pavicic, Tatjana; Kühne, Ulrich; Kravtsov, Maria; Hofmann, Matthias; Dersch, Hanna; Sattler, Sonja
Abstract : Background: There is a growing interest in the application of hyaluronic acid (HA) derivatives in skin quality improvement. The aim of this study was to confirm safety and effectiveness of cohesive polydensified matrix-hyaluronic acid + glycerol (CPM-HA20G; Belotero Revive) in revitalization of early-onset photodamaged facial skin. Methods: A total of 159 subjects with early signs of facial photodamaged skin were randomized in a 2:1 ratio to multiple- or single-dose treatment with CPMHA20G. Effectiveness assessments included biophysical measurements of skin hydration; elasticity, firmness, and roughness; investigator- and subject-assessed Global Aesthetic Improvement Scales; and FACE-Q Skin Changes and Treatment Satisfaction questionnaires. Results: In both treatment groups, skin hydration improved from baseline to all follow-up visits in subjects with dry or very dry skin. This improvement was significant at week 16 after initial treatment in the multiple-dose group ( P = 0.0013). Investigator- and subject-reported outcomes showed that the majority of subjects across all skin hydration types benefited from treatment, with higher satisfaction rates observed in the multiple-dose group. According to investigator-assessed Global Aesthetic Improvement Scale, 90.7% of subjects at week 12 in the multiple-dose and 74.6% of subjects at week 4 in the single-dose group were rated as at least "improved." All related treatment-emergent adverse events were transient, expected injection-site reactions of mild to moderate intensity. Conclusions: Effectiveness of CPM-HA20G for skin hydration in subjects with dry or very dry skin was demonstrated up to 9 months after last injection. Overall, CPM-HA20G demonstrated effective and safe use in facial skin revitalization among subjects with early-onset photodamaged skin.